The Violation of the Dignity of the Advocate Profession in the Perspective of Deontological Ethics Immanuel Kant: A Philosophical and Juridical Study of the Phenomenon of "Lawyers at the Table" - Alex Togaraja Simanjorang; Wa Marcella; Hendriadi Yustin; Ranny Iwan Susilo; Hernawati RAS (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This study aims to analyze the violation of the ethics of the advocate profession which is metaphor as the phenomenon of "Lawyer at the Table" through the perspective of Immanuel Kant's deontological morality. The research uses normative legal research methods with legislative, conceptual, and philosophical approaches, and is analyzed qualitatively through literature studies. The results of the study show that the phenomenon reflects the crisis of moral obligations in the practice of the legal profession which is characterized by the dominance of instrumental rationality, the weak internalization of professional ethics, and the shift in professional orientation from moral obligations to pragmatic interests. Based on Kant's theory of deontology, these actions are contrary to the principle  of categorical imperative, especially the Universality Formula and the Humanity Formula, because they cannot be universalized as moral law and reduce human dignity and judicial institutions as a means of certain interests. This study also found that resolving violations of the ethics of the advocate profession is not enough through a disciplinary sanctions approach, but requires the reconstruction of professional ethics through the universalization of actions, respect for human dignity, and the internalization of universal moral obligations. The implications of the study confirm that Immanuel Kant's deontological theory is relevant as a philosophical foundation for establishing universal, rational, and justice-oriented standards of ethics for the legal profession.